THE ROLE OF ZERO ACCIDENTS ON EMPLOYEE PERFORMANCE - Ikram Nawawi; Kiki Farida Ferine; Sri Rahayu (Universitas Efarina, 2025)
This study aims to analyze the influence of work environment and work discipline on employee performance through zero accidents as a mediating variable. The research was conducted at PT PLN (Persero) ULP Matang Glumpang Dua UP3 Lhokseumawe UID Aceh, with a population and sample of 39 employees, using a saturated sampling technique since the entire population was included as respondents. The data analysis method used was Structural Equation Modeling (SEM) with the Partial Least Square (PLS) approach. The results showed that both work environment and work discipline have a positive and significant effect on employee performance. Furthermore, work environment and work discipline also have a positive and significant effect on zero accidents. The zero accident variable is proven to positively and significantly affect employee performance. Additionally, zero accidents significantly mediates the effect of work environment and work discipline on employee performance. These findings emphasize the importance of creating a safe work environment and fostering employee discipline to achieve optimal performance.